The Relationship between Marketing Mix and Purchase Decision Process Via Smartphone of Modern Consumers in The Ministry of - Sanglien, Wutiporn; Boonyasirinun, Luxanwadee (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
The objectives of this research were 1) to study the level of opinions of modern consumers in the marketing mix in purchase decision products via smartphone. 2) To study the opinion levels of the decision-making process of purchase decision process products via smartphone of modern consumers in the Ministry of Commerce. 3) The relationship of comments to the marketing mix to process a purchase through a smartphone or the modern consumers. The sample group was the person who works at the Ministry of Commerce Nonthaburi Province, aged 20- 37 years, the sample size was 318 persons, and used probability sampling method for Collecting data by using questionnaires for analysis such as frequency, percentage, mean and standard deviation. The hypothesis testing statistics use Pearson’s correlation coefficient. The research results revealed that the marketing mix of 4 C’s (4 C’s Marketing) of modern consumers in the Ministry of Commerce Nonthaburi Province overall, the average score was at the highest level (mean=4.91). Decision-making process Shop through your smartphone of consumers in the new era in the Ministry of Commerce Nonthaburi Province overall had the highest average score (mean=4.91) and the relationship between marketing mix 4C’s (4 C’s Marketing) to process a purchase via smartphone modern consumers in the Ministry of Commerce, Nonthaburi overall relationship. moderately (r=0.527).